Galanin‐like immunoreactivity in the brain of teleosts : Distribution and relation to substance P, vasotocin, and isotocin in the atlantic salmon (Salmo salar) - Holmqvist, Bo I.; Ekström, Peter (Journal of Comparative Neurology, 1991)
The presence of galanin‐like substances and their relation to substance P‐, vasotocin‐, and isotocin‐immunoreactive neurons and fibers in the brain of teleosts was investigated with immunohistochemical methods. Two specific antisera against synthetic porcine galanin (GAL) revealed cell bodies and fibers in the brain of four different teleost species (Salmo salar, Carassius carassius, Gasterosteus aculeatus, and Anguilla anguilla). In all four species the main location of galanin immunoreactivity was in the hypothalamo‐pituitary region. A detailed study of the distribution of galanin immunoreactivity in S. salar showed that galanin immunoreactive (GALir) perikarya were present in the nucleus preopticus periventricularis, an area that may be compared to the supraoptic nucleus in mammals, and in the nucleus lateralis tuberis, a nucleus involved in pituitary control in fishes that may be compared with the arcuate nucleus in mammals, GALir perikarya were found also in the nucleus recessus lateralis and in the nucleus recessus posterior. Numerous GALir fibers were present in the telencephalon and diencephalon, whereas only small numbers of fibers were found in the brainstem. In contrast to the situation in mammals, no GALir perikarya were observed in the brainstem areas corresponding to the noradrenergic locus coeruleus and serotonergic raphe nuclei in S. salar. We did not find any coexistence of GALir substances with arginine vasotocin or isotocin in neurosecretory neurons, as has been shown for galanin with the mammalian counterparts vasopressin and oxytocin. Also, the galanin‐like substance(s) and their structurally closest related peptide family, the tachykinins, belong to separate neuronal systems in teleosts. The presence of GALir neurons in brain areas known to be involved in pituitary control, and a massive GALir innervation of the pituitary, strongly indicate a role for galanin‐like substances in pituitary control also in teleosts. Furthermore, the presence of extrahypothalamic GALir fibers suggests ...